STUDY OF QUERCETIN DIHYDRATE EFFECTS IN A MODEL OF OVA-INDUCED RESPIRATORY ALLERGY IN MICE - A. O. Kenkishvili (SPb RAACI, 2017)
We have investigated in vivo effects of quercetin dihydrate (QD) upon course of respiratory allergy produced in experimental murine model. To provoke allergy, serum ovalbumin (OVA) was injected at different terms. Following administration of QD at the stage of OVA sensitization, the balance of T-helper cytokines was changed (IL-2 was decreased along with increased IFNγ) accompanied by decreased allergen-specific IgG1, IgE and increased IgG2a in blood serum. At the stage of boosting the respiratory allergy, intravenous administration of QD caused reduction of inflammatory lung infiltration, and composition of bronchoalveolar lavage fluid was altered, i.e., IgG1 and IgE showed a decrease, along with higher IgG2a levels.